Rubbing time and bonding performance of one-step adhesives to primary enamel and dentin - Botelho, Maria Paula Jacobucci; Isolan, Cristina Pereira; Schwantz, Júlia Kaster; Lopes, Murilo Baena; Moraes, Rafael Ratto de (Journal of Applied Oral Science, 2017)
Objectives: This study investigated whether increasing the concentration of acidic monomers in one-step adhesives would allow reducing their application time without interfering with the bonding ability to primary enamel and dentin. Material and methods: Experimental one-step self-etch adhesives were formulated with 5 wt% (AD5), 20 wt% (AD20), or 35 wt% (AD35) acidic monomer. The adhesives were applied using rubbing motion for 5, 10, or 20 s. Bond strengths to primary enamel and dentin were tested under shear stress. A commercial etch-and-rinse adhesive (Single Bond 2; 3M ESPE) served as reference. Scanning electron microscopy was used to observe the morphology of bonded interfaces. Data were analysed at p